Extramedullary Plasmacytoma of the Maxillary Sinus with Intra-Orbital Extension: A Case Report of a Rare Condition - Sharouny, Hadi; Taheri, Abolfazl; Shamsaei, Hassan (Reports of Radiotherapy and Oncology, 2019)
Introduction: The most common site for extramedullary plasmacytomas (EMP) is the upper respiratory tract, including the oropharyngeal and nasal cavities, paranasal sinuses, and larynx. The EMPs of the head and neck area are uncommon malignancies comprising only 3% to 4% of all the plasmacytomas. Case Presentation: We presented a 78-year-old man with right facial swelling, right exophthalmos, diplopia, and decrease in visual acuity of the right eye for three weeks. A right nasal mass was identified on nasal endoscopic examination. Computed tomography scan of the paranasal sinuses revealed a mass in the right maxillary and ethmoid sinuses with orbital extension. Histopathologic examination showed plasmacytoma of paranasal sinuses. Patient received 56 Gy in 28 fractions of radiotherapy. He was well in the follow-up visits during the next one year. Conclusions: Although sinonasal EMP is rare, it is worth being considered in the differential diagnoses of paranasal malignancies. Radiotherapy is the treatment of choice for solitary EMPs of paranasal sinuses. Long-term follow-up is essential in EMPs.